A descriptive analysis of where and with whom lesbian versus bisexual women drink. Issue 4 (2nd October 2017) - Feinstein, Brian A.; Bird, Elizabeth R.; Fairlie, Anne M.; Lee, Christine M.; Kaysen, Debra
ABSTRACT: Sexual minority women (SMW) are at increased risk for alcohol use disorders and related problems. Social context (e.g., where and with whom one drinks) has been identified as an important factor associated with drinking behavior, but little is known about social context among SMW. An improved understanding of social context among SMW has the potential to inform efforts to reduce problematic drinking and its consequences in this high-risk population. We examined where and with whom SMW drink in a national sample recruited via social media ( N = 1, 057). SMW reported more frequent drinking in private locations (compared to public locations), with friends and romantic partners (compared to family members and strangers), and in locations with both heterosexual and sexual minority individuals (compared to mostly or exclusively sexual minority individuals). Additionally, lesbians reported more frequent drinking in bars and in locations with more sexual minorities compared to bisexual women. We conclude that interventions to reduce problematic drinking among SMW may benefit from addressing social context.